Demographic Losses Due To Alcohol-Related Mortality in Lithuania: Results Obtained Through Combining Death Records with the 2011 Population Census Data - Stumbrys, Daumantas; Jasilionis, Domantas; Ambrozaitienė, Dalia; Stankūnienė, Vlada (Lithuanian Journal of Statistics, 2014)
This paper presents the results of a study on sociodemographic mortality differentials in Lithuania based on censuslinked mortality data. Population data come from the individual records of the 2011 Population and Housing Census of the Republic of Lithuania. The results of the research demonstrate that education and marital status are very strong predictors of alcohol-related mortality. Among males aged 30 and older, the alcohol-related mortality risk in non-married groups is up to 3.4 times as high as in the group of married males. The alcohol-related mortality risk in lower-education groups is up to 3.7 times as high as in the group of those with higher education. The findings of the study suggest that the elimination of educational differences would allow avoiding 55.7 %, the elimination of marital status differences – 40.2 %, the elimination of ethnic group differences – 11.1 % of alcohol-related deaths.
Keywords: alcohol; census-linked; mortality differentials